Difficulty in Diagnosing Peritoneal Fluid Cytology in Ovarian Yolk Sac Tumor Cases - Pemuda, Haris; Yenita, Yenita; Mayorita, Pamelia; Setiawati, Yessy; Muhammad, Syamel (Fakultas Kedokteran Universitas Andalas, 2021)
Objective : This article objective is to describe cytology diagnosis difficulties of yolk sac tumors of the ovary.Method : Case reports and literature review.Case : The author reports the case of a 24 year old woman who complained of an enlarged stomach. Serum AFP increased to 16,519.7 U/mL. Ultrasound examination revealed solid and irregular mass of ovarian, so the conclusion was suspect ovarian carcinoma. Conclusion of CT scan examination was a solid ovarian tumor. The working diagnosis was suspect ovarian carcinoma. Optimal debulking was performed, accompanied by taking a sample from the peritoneal rinse fluid. Microscopic examination of peritoneal fluid showed the distribution and group of cells with pleomorphic nuclei, partly hyperchromatic, partly vesicular with coarse chromatin and prominent nucleoli. There were also cells with polygonal nuclei, small nuclei, basophilic and vacuole cytoplasm with a mucoid background. These cells formed a solid arrangement. Conclusion from these features was carcinoma metastases to the peritoneal fluid. Microscopic examination from tumor tissue sample showed an ovarian yolk sac tumor appearance.Conclusion : Cytologic examination of peritoneal fluid in cases of ovarian yolk sac tumor is quite difficult to determine the diagnosis. This is due to the microscopic appearance of tumor cells which often looks like a carcinoma and limited literature about this tumors in the peritoneal fluid.Keywords: Yolk sac tumor, ovary,Â